PENGARUH PENDEKATAN STEM BERBASIS LITERASI DAN NUMERASI TERHADAP MATERI SISTEM PERNAPASAN PADA MANUSIA SISWA FASE C SD N SAMPANGAN 01 - Lustania, Desi; Patonah, Siti; Suyitno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy and numeracy are two basic skills that are very important for every individual in facing future challenges. This study is motivated by the low literacy and numeracy skills of students in IPAS subjects. The purpose of this study was to determine the effect of STEM approach based on literacy and numeracy on human respiratory system material in phase C students of SD N Sampangan 01. This study used pre-test and post-test methods, and quasi-experiment using a nonequivalent control group design pattern. The average results of students' posttest scores after being given treatment using the STEM approach. The results of this study indicate that there is an influence between the results of the pre-test and post-test used to measure numeracy literacy skills with the STEM approach. This is evidenced by the results of data analysis using the t test, which shows a significance value of 0.000 < 0.05. Thus, the decision taken is to reject H0 and accept Ha, which means that there is a significant difference between students' literacy and numeracy skills before and after the application of the STEM approach with the PjBL learning model.